A skeletal Class III malocclusion with agenesis and canine-bicuspid transposition: a non-surgical approach - Bellot-Arcís Carlos; García-Sanz Veronica; Paredes-Gallardo Vanessa (Sciendo, 2018)
The present case report describes the orthodontic management of a patient who presented with a skeletal Class III malocclusion combined with other dental anomalies. The malocclusion was complicated by agenic maxillary lateral incisors and a lower right second premolar, in company with the transposition of the maxillary canines and premolars.